Optical switching of polariton density patterns in a semiconductor microcavity. (13th February 2017) - Kwong, N H; Tsang, C Y; Luk, Samuel M H; Tse, Y C; Chan, Chris K P; Lewandowski, P; Leung, P T; Schumacher, Stefan; Binder, R
Abstract: Phase-conjugate scattering can trigger modulational instabilities in a fluid of exciton-polaritons created in a pumped semiconductor quantum-well microcavity. These instabilities can settle into density patterns, e.g. hexagons and stripes, which produce corresponding patterns in the emitted light. The density patterns can be switched by relatively weak control optical beams. This paper reviews progress in our theoretical understanding of the physical processes that regulate the competitions among various patterns and drive the optical switching. Simulation results of pattern switching using a microscopic model of polariton dynamics are shown, and the mechanisms underlying competitions and switching are analyzed using reduced models that restrict the polariton motions to a limited number of relevant modes. We also briefly indicate the effects of the spin dependence of the polariton dynamics on the patterns.